Digital Literacy in Education and Humanities under the Covid-19 Pandemic: A Preliminary Identification of Challenges and Opportunities - Maksimus Regus (Budapest International Research and Critics University, 2022)
The COVID-19 pandemic broadly presents a series of crucial impacts on human life. COVID-19 is transforming the fundamental dimensions of education and humanities. Digitization and technology are new demands in educational practice under COVID-19. Therefore, digital literacy is an absolute prerequisite in this new era of educational practice. This paper identifies explicitly and reflects on the opportunities and challenges of digital literacy from education and humanities in the setting of the COVID-19 pandemic. However, this paper is only limited to a general overview of previous studies on digital literacy concerning the impact of COVID-19 in education and humanities.